Adipose tissue R2* signal is increased in subjects with obesity: A preliminary MRI study. (26th December 2015) - Manuel Fernández‐Real, José; Blasco, Gerard; Puig, Josep; Moreno, Maria; Xifra, Gemma; Sánchez‐Gonzalez, Javier; Maria Alustiza, Jose; Pedraza, Salvador; Ricart, Wifredo; María Moreno‐Navarrete, José
Abstract : Objective : Circulating and adipose tissue markers of iron overload are increased in subjects with obesity. The aim is to study iron signals in adipose tissue. Methods: Adipose tissue R2* values and hepatic iron concentration (HIC) were evaluated using magnetic resonance imaging (MRI) in 23 middle‐aged subjects with obesity and 20 subjects without obesity. Results: Subcutaneous (SAT) and visceral adipose tissue (VAT) R2* were increased in subjects with obesity ( P = 0.004 and P = 0.008) and correlated significantly and positively with HIC in all subjects. Strikingly, most of the associations of liver iron with metabolic parameters were replicated with SAT and VAT R2*. BMI, waist circumference, fat mass, HOMA value, and C‐reactive protein positively correlated with HIC and SAT and VAT R2*. BMI or percent fat mass (but not insulin resistance) contributed independently to 26.8‐34.8% of the variance in sex‐ and age‐adjusted SAT or VAT R2* ( β > 0.40, P < 0.005). Within subjects with obesity, total cholesterol independently contributed to 14.8% of sex‐ and age‐adjusted VAT iron variance ( β = 0.50, P = 0.025). Conclusions: Increased R2* in adipose tissue, which might indicate iron content, runs in parallel to liver iron stores of subjects with obesity. VAT iron seems also associated with serum cholesterol within subjects with obesity.